SELECTING AN OPTIMAL LONG-TERM ANTICOAGULANT THERAPY FOR A PATIENT WITH ATRIAL FIBRILLATION AND RECURRENT MINOR HEMORRHAGE. CLINICAL FOLLOW-UP - E. S. Kropacheva; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2017)
For patients with atrial fibrillation, long-term oral anticoagulant therapy reduces the risk of ischemic stroke and systemic embolism, while increasing the risk of hemorrhagic complications. To assess the safety of therapy, along with major bleeding, minor and clinically relevant bleeding also should be taken into account. Minor, especially recurrent hemorrhages usually do not provide a reason for discontinuing anticoagulant therapy. The described follow-up demonstrated the absence of major hemorrhage in the patient with recurrent minor hemorrhagic complications against a background of 15-year course of anticoagulant therapy (including 9-year course of dabigatran treatment).